197k views
4 votes
Complete the proof of the identity by choosing the Rule that justifies each step.(sec^2x-1) cosx = sin^2x secxTo see a detailed description of a Rule, select the More Information Button to the right of the Rule.

Complete the proof of the identity by choosing the Rule that justifies each step.(sec-example-1
User PovilasB
by
6.2k points

1 Answer

4 votes

From the question we are to complete the proof


(sec^2x-1)\cos x=\sin ^2x\sec x

Solving LHS

By applying Pythagorean rule


1+\tan ^2x=\sec ^2x

This implies


\tan ^2x=\sec ^2x-1

Therefore we have


(\sec ^2x-1)\cos x=\tan ^2x\cos x

User MadMac
by
5.7k points